A kind of self-adhesive label and its preparation method and application
By using a variety of raw materials of a specific proportion in the self-adhesive adhesive, the problems of low adhesion strength, poor anti-aging and easy cracking of existing self-adhesive labels are solved, and efficient anti-aging, thermal stability and adhesion performance are achieved, which is suitable for large-scale production and practical applications.
Patent Information
- Application Number
- CN202411282388.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing self-adhesive labels have defects such as low adhesion strength, poor anti-aging and prone to cracking, and their performance has not been fully improved.
Self-adhesive adhesives are prepared using specific proportions of methacrylic acid, polyvinyl alcohol, strong polar monomers, polyoctene copolymer emulsions, nanomicrocrystalline cellulose, modified nanotitanium dioxide, ultraviolet absorbers and dispersants. Through the synergistic effect of these components, the adhesive strength, anti-aging properties and flexibility of the adhesive are improved.
The prepared self-adhesive adhesive has excellent anti-aging, thermal stability and adhesion strength, and is not easy to crack. It is suitable for large-scale production and shows high durability and reliability in practical applications.
Smart Images

Figure BDA0005042061700000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of label stickers, and in particular to a self-adhesive sticker and a preparation method and application thereof. Background Art
[0002] Since the advent of self-adhesive labels, the demand for this composite material has increased year by year with the demand in daily life and industry. The application of self-adhesive labels has developed rapidly. At present, it is widely used in various packaging of food, alcohol, beverages and pharmaceutical products. According to data, my country is also a huge label consumption market. Statistics in the past five years show that each person consumes about 2.5 square meters of self-adhesive label materials throughout the year. Existing self-adhesive labels have defects such as low adhesion strength, poor anti-aging and easy cracking, and their performance still has a lot of room for improvement. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present application provides a self-adhesive sticker and a preparation method and application thereof. The self-adhesive sticker prepared by the present application has excellent anti-aging performance, thermal stability and adhesion strength, and is not easy to crack. In addition, the preparation method of the present application is simple and easy to implement, and is suitable for large-scale production.
[0004] In the first aspect, the present application provides a self-adhesive sticker, which adopts the following technical solution:
[0005] A self-adhesive sticker, wherein the structural layers of the self-adhesive sticker sequentially include a surface layer, an adhesive layer and a bottom layer from top to bottom; wherein the adhesive layer is prepared from an adhesive, and the adhesive includes the following preparation raw materials, measured by weight: 70-75 parts of methacrylic acid, 0.6-0.8 parts of polyvinyl alcohol, 9-11 parts of strong polar monomers, 50-55 parts of polyoctene copolymer emulsion, 4-5 parts of nano-microcrystalline cellulose, 20-24 parts of modified nano-titanium dioxide, 2.6-2.8 parts of an initiator aqueous solution, 0.8-1.2 parts of an ultraviolet absorber, 0.3-0.5 parts of a dispersant, and 200-210 parts of deionized water.
[0006] By adopting the above technical scheme, methacrylic acid is used as the main raw material of the adhesive to provide the basic bonding properties of the adhesive. Polyvinyl alcohol is used as a thickener to adjust the viscosity of the adhesive and make it easier to apply. Strong polar monomers introduce strong polar groups such as amino and amide groups to enhance the bonding strength of the adhesive and form ionic bonds, hydrogen bonds and other forces with oxygen-containing groups on the surface of the surface layer and the bottom layer. The polyoctene copolymer emulsion provides a long-chain non-polar octane group, which increases the flexibility of the adhesive and makes the self-adhesive adhesive less likely to crack. Nanocrystalline cellulose has good compatibility with the various components of the adhesive, which improves the bonding strength and thermal stability of the adhesive. Modified nano titanium dioxide is an effective ultraviolet absorber, which can absorb ultraviolet rays and reduce the photodegradation of the self-adhesive adhesive caused by UV, thereby improving the anti-aging of the self-adhesive adhesive. The initiator aqueous solution is used to initiate the polymerization reaction. The ultraviolet absorber can absorb solar ultraviolet radiation, prevent ultraviolet rays from irradiating and damaging the self-adhesive adhesive, and improve the comprehensive performance of the self-adhesive adhesive. The dispersant is used to improve the dispersibility of nanoparticles in the adhesive. Deionized water is used as a solvent. In summary, through the synergistic effect of the above components, the self-adhesive prepared in the present application has excellent anti-aging, thermal stability and adhesion strength, and is not easy to crack. In addition, the preparation method of the present application is simple and easy to implement, and is suitable for large-scale production.
[0007] Preferably, the highly polar monomer is composed of hydroxyethyl methacrylate, methacrylamide and dimethylaminoethyl methacrylate in a mass ratio of 1:1:3.
[0008] By adopting the above technical scheme, the role of strong polar monomers in adhesives is to enhance the bonding strength. They form ionic bonds, hydrogen bonds and other forces with oxygen-containing groups on the surface of the surface layer and the bottom layer by introducing strong polar groups such as amino groups and amide groups, thereby improving the bonding strength of the adhesive. Hydroxyethyl methacrylate (HEMA) is a monomer containing hydroxyl groups, which can chemically react with oxygen-containing groups on the surface of the surface layer and the bottom layer to form covalent bonds. In addition, HEMA can also copolymerize with other monomers to form polymers with higher molecular weights, thereby improving the bonding strength of the adhesive. Methacrylamide (MAA) is a monomer containing amide groups, which can hydrogen bond with oxygen-containing groups on the surface of the surface layer and the bottom layer. At the same time, MAA can also copolymerize with other monomers to form polymers with higher molecular weights, thereby improving the bonding strength of the adhesive. Dimethylaminoethyl methacrylate (DMAEMA) is a monomer containing tertiary amine groups, which can ionic bond with oxygen-containing groups on the surface of the surface layer and the bottom layer. In addition, DMAEMA can also copolymerize with other monomers to form polymers with higher molecular weight, thereby improving the bonding strength of the adhesive. In summary, these three strong polar monomers, through their own characteristics and synergistic effects, jointly improve the bonding strength of the adhesive, making the self-adhesive have excellent anti-aging, thermal stability and adhesion strength, and are not easy to crack.
[0009] Preferably, the preparation method of the polyoctene copolymer emulsion is as follows: 390 parts of deionized water and 0.6 parts of sodium dodecylbenzene sulfonate are added to a glass reactor according to their weight fractions, high-purity nitrogen is introduced, and the mixture is stirred at a stirring speed of 300 rpm for 1-1.5 hours, and then 18 parts of 1-octene are added, and the mixture is stirred at a stirring speed of 300 rpm for 0.5-0.7 hours, the mixture is heated to 60° C. and kept at a constant temperature, and then 1 part of an initiator aqueous solution with a mass concentration of 20% is added and reacted at 60° C. for 2-2.5 hours, and then 68 parts of 1-octene, 16 parts of perfluoromethyl vinyl ether, and 5 parts of an ammonium persulfate aqueous solution with a mass concentration of 20% are respectively added dropwise to the reactor through a peristaltic pump, the addition time is 3.5 hours, the mixture is reacted at 60° C. for 5-6 hours, the reaction is cooled to room temperature after the reaction is completed, and the mixture is filtered through a 150-mesh screen to obtain the polyoctene copolymer emulsion.
[0010] By adopting the above technical scheme, the polyoctene copolymer emulsion provides long-chain non-polar octane groups. These long-chain structures can form a "buffer layer" in the adhesive. When the self-adhesive is subjected to external forces or environmental changes, this "buffer layer" can absorb and disperse the effects of these changes, thereby protecting the adhesive from being destroyed, so that the self-adhesive maintains good adhesion properties and is not easy to crack. In addition, the polyoctene copolymer emulsion also has a good synergistic effect with other components. For example, it can enhance the bonding strength of the adhesive together with the strong polar monomer. The strong polar monomer introduces strong polar groups such as amino and amide groups, which enhance the bonding strength of the adhesive and form ionic bonds, hydrogen bonds and other forces with the oxygen-containing groups on the surface of the surface layer and the bottom layer, while the polyoctene copolymer emulsion provides flexibility. The combination of the two makes the adhesive have both good adhesion properties and sufficient flexibility, and is not easy to crack.
[0011] Preferably, the preparation method of the modified nano titanium dioxide comprises the following steps:
[0012] S41. Fully mix hexamethyldisilazane, 3-aminopropyltrimethoxysilane, tetraethoxysilane and anhydrous ethanol according to their weight fractions to prepare a mixed modifier;
[0013] S42. According to the mass proportions, 100 parts of nano titanium dioxide with a particle size of 10 nm and 200 parts of mixed modifier are fully mixed at room temperature for 50-60 minutes, ultrasonicated at room temperature for 1-2 hours, and then transferred into a vacuum mixer. The mixture is heated to 85°C and stirred at -0.5 MPa for 4-5 hours under reflux conditions. Finally, ethanol is removed under reduced pressure and dried to obtain modified nano titanium dioxide.
[0014] By adopting the above technical scheme, the prepared modified nano titanium dioxide acts as an effective ultraviolet absorber, which can absorb ultraviolet rays and reduce the photodegradation of self-adhesive stickers caused by UV, thereby improving the anti-aging of self-adhesive stickers. Through the reaction with hexamethyldisilazane, 3-aminopropyltrimethoxysilane and tetraethoxysilane, the surface of nano titanium dioxide is modified to make it have stronger hydrophobic and oil-resistant properties. Through surface modification, the compatibility and dispersibility of nano titanium dioxide in adhesives are improved, thereby enhancing the anti-aging, thermal stability and adhesion strength of adhesives.
[0015] Preferably, the mass ratio of hexamethyldisilazane, 3-aminopropyltrimethoxysilane, tetraethoxysilane and anhydrous ethanol is 2:3:2:100.
[0016] Preferably, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a mass ratio of 3:4.
[0017] By adopting the above technical solution, dioctadecyl pentaerythritol phosphate is a highly efficient organophosphorus ultraviolet absorber, which can absorb harmful bands in ultraviolet rays, especially UVA and UVB regions, and reduce the impact of these ultraviolet rays on adhesives. BASF's light stabilizer CHIMASSORB944 is an inorganic type of ultraviolet absorber, which can also absorb UVA and UVB, and has better thermal stability and chemical stability than organic compounds. When these two ultraviolet absorbers are mixed in a specific proportion, a synergistic effect will occur between them, that is, the effects of the two compounds are superimposed, so that the anti-ultraviolet ability of the self-adhesive is further enhanced. This synergistic effect not only improves the weather resistance of the self-adhesive and extends the service life of the product, but also reduces the color change and material embrittlement caused by ultraviolet radiation, thereby ensuring that the self-adhesive can maintain good performance in various environments. In addition, this combination of ultraviolet absorbers also helps to improve the overall stability and reliability of the self-adhesive, making it more durable and reliable in practical applications.
[0018] Preferably, the dispersant is composed of sodium dodecylbenzene sulfonate, sodium diethylhexyl sulfosuccinate and octylphenol polyoxyethylene (10) ether in a mass ratio of 4:5:6.
[0019] By adopting the above technical scheme, the main role of the dispersant in the preparation of the adhesive is to improve the dispersibility of nanoparticles and other solid particles in the liquid medium, prevent the particles from aggregating and settling, and thus ensure the uniformity and stability of the adhesive. Sodium dodecylbenzene sulfonate is an anionic surfactant that can reduce surface tension, promote the wetting of nanoparticles and solid particles, and facilitate the dispersion of these particles in the liquid medium. Sodium diisooctyl sulfosuccinate is also an anionic surfactant. Its molecular structure contains two hydrophobic groups, which can provide a stronger steric hindrance effect, reduce the interaction between particles, and prevent particle aggregation. Octylphenol polyoxyethylene (10) ether is a nonionic surfactant. Its hydrophilic group can form hydrogen bonds with water molecules, while the hydrophobic group can interact with the particle surface, thereby stabilizing the dispersion state of the particles in the liquid. The combined use of these three dispersants can make full use of their respective advantages, act on the particle surface through different mechanisms, and achieve a more effective dispersion effect. This synergistic effect not only improves the overall performance of the adhesive, but also helps to improve its processing performance and application performance, such as anti-aging, thermal stability and adhesion strength.
[0020] Preferably, the mass concentration of the initiator aqueous solution is 18%, and the initiator is sodium persulfate.
[0021] In a second aspect, the present application provides a method for preparing a self-adhesive sticker, using the following technical solution:
[0022] As a general technical concept, the present application also provides a method for preparing the above-mentioned self-adhesive sticker, comprising the following steps:
[0023] S91. Add deionized water and polyvinyl alcohol in a glass reactor according to their mass fractions, introduce high-purity nitrogen, stir at a stirring speed of 350 rpm for 1-1.2 h, then add methacrylic acid, strong polar monomer, polyoctene copolymer emulsion, nano-microcrystalline cellulose, modified nano-titanium dioxide, ultraviolet absorber and dispersant in sequence, raise the temperature to 60°C and keep the temperature constant; then add an initiator aqueous solution to initiate the reaction, stop heating after the reaction for 9 hours, cool to room temperature, filter, wash, dry, crush and sieve to obtain an adhesive;
[0024] S92, applying adhesive on the surface of the surface layer to obtain an adhesive layer;
[0025] S93, the adhesive layer is combined with the bottom layer, and dried to obtain a self-adhesive label.
[0026] In a third aspect, the present application provides an application of a self-adhesive sticker, using the following technical solution:
[0027] As a general technical concept, the present application also provides the application of the above-mentioned self-adhesive sticker in a label sticker.
[0028] In summary, the present application includes at least one of the following beneficial technical effects:
[0029] 1. Excellent anti-aging performance: Through the combined effect of modified nano titanium dioxide and ultraviolet absorber, it effectively absorbs ultraviolet radiation, reduces photodegradation, and improves the anti-aging performance of the self-adhesive label.
[0030] 2. Good thermal stability: Nano-microcrystalline cellulose has good compatibility with the components of the adhesive, which improves the bonding strength and thermal stability of the adhesive, allowing the self-adhesive to maintain good adhesion properties in a high temperature environment.
[0031] 3. High adhesion strength: Strong polar monomers introduce strong polar groups such as amino and amide groups, which enhance the bonding strength of the adhesive and form ionic bonds, hydrogen bonds and other forces with the oxygen-containing groups on the surface of the surface layer and the bottom layer, thereby improving the adhesion strength of the self-adhesive.
[0032] 4. Not easy to crack: Polyoctene copolymer emulsion provides long-chain non-polar octane groups, which increases the flexibility of the adhesive and makes the self-adhesive adhesive less likely to crack during use.
[0033] 5. The preparation method is simple and easy: The preparation method of the present application is simple and easy, suitable for large-scale production, and is conducive to reducing production costs and improving production efficiency. DETAILED DESCRIPTION
[0034] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0035] In the following examples and preparation examples, 1 part means 50 g.
[0036] Preparation Example 1 Preparation of polyoctene copolymer emulsion
[0037] The preparation method of the polyoctene copolymer emulsion is as follows: 390 parts of deionized water and 0.6 parts of sodium dodecylbenzene sulfonate are added to a glass reactor according to the weight fractions, high-purity nitrogen is introduced, and the mixture is stirred at a stirring speed of 300 rpm for 1.3 hours, and then 18 parts of 1-octene are added, and the mixture is stirred at a stirring speed of 300 rpm for 0.6 hours, the mixture is heated to 60° C. and kept at a constant temperature, and then 1 part of an initiator aqueous solution with a weight concentration of 20% is added, and the mixture is reacted at 60° C. for 2.3 hours, and then 68 parts of 1-octene, 16 parts of perfluoromethyl vinyl ether, and 5 parts of an ammonium persulfate aqueous solution with a weight concentration of 20% are respectively added dropwise to the reactor through a peristaltic pump, the addition time is 3.5 hours, the mixture is reacted at 60° C. for 5.5 hours, the mixture is cooled to room temperature after the reaction is completed, and the mixture is filtered through a 150-mesh screen to obtain the polyoctene copolymer emulsion.
[0038] Preparation Example 2 Preparation of modified nano titanium dioxide
[0039] The preparation method of modified nano titanium dioxide comprises the following steps:
[0040] S41. According to the mass ratio, 4 parts of hexamethyldisilazane, 6 parts of 3-aminopropyltrimethoxysilane, 4 parts of tetraethoxysilane and 200 parts of anhydrous ethanol are fully mixed to prepare a mixed modifier;
[0041] S42. According to the mass proportions, 100 parts of nano titanium dioxide with a particle size of 10 nm and 200 parts of mixed modifier were fully mixed at room temperature for 55 minutes, and then ultrasonicated at room temperature for 1.6 hours, and then transferred into a vacuum mixer. The mixture was heated to 85°C and stirred at -0.5 MPa for 4.5 hours under reflux conditions. Finally, the ethanol was removed under reduced pressure and dried to obtain modified nano titanium dioxide.
[0042] Example 1
[0043] A self-adhesive sticker, wherein the structural layers of the self-adhesive sticker include, from top to bottom, a surface layer (thermal paper with a thickness of 20 μm), an adhesive layer and a bottom layer (wax paper with a thickness of 10 μm); wherein the adhesive layer is prepared from an adhesive, and the adhesive includes, by weight, the following raw materials: 70 parts of methacrylic acid, 0.6 parts of polyvinyl alcohol, 9 parts of a strong polar monomer, 50 parts of a polyoctene copolymer emulsion, 4 parts of nano-microcrystalline cellulose, 20 parts of modified nano-titanium dioxide, and 2.6 parts of an aqueous sodium persulfate solution with a mass concentration of 18%. , 0.8 parts of ultraviolet absorber, 0.3 parts of dispersant, and 200 parts of deionized water, the strong polar monomer consists of hydroxyethyl methacrylate, methacrylamide and dimethylaminoethyl methacrylate in a mass ratio of 1:1:3, the ultraviolet absorber consists of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a mass ratio of 3:4, and the dispersant consists of sodium dodecylbenzene sulfonate, sodium diethyl sulfosuccinate and octylphenol polyoxyethylene (10) ether in a mass ratio of 4:5:6.
[0044] The above-mentioned method for preparing a self-adhesive label comprises the following steps:
[0045] S91. Add deionized water and polyvinyl alcohol in a glass reactor according to their mass fractions, introduce high-purity nitrogen, stir at a stirring speed of 350 rpm for 1 hour, then add methacrylic acid, strong polar monomer, polyoctene copolymer emulsion, nano-microcrystalline cellulose, modified nano-titanium dioxide, ultraviolet absorber and dispersant in sequence, heat to 60°C and keep the temperature constant; then add sodium persulfate aqueous solution with a mass concentration of 18% to initiate the reaction, stop heating after the reaction for 9 hours, cool to room temperature, filter, wash, dry, crush and sieve to obtain an adhesive;
[0046] S92, applying adhesive on the surface of the surface layer to obtain an adhesive layer;
[0047] S93, the adhesive layer is combined with the bottom layer, and dried to obtain a self-adhesive label.
[0048] Example 2
[0049] A self-adhesive sticker, wherein the structural layers of the self-adhesive sticker include, from top to bottom, a surface layer (thermal paper with a thickness of 20 μm), an adhesive layer and a bottom layer (wax paper with a thickness of 10 μm); wherein the adhesive layer is prepared from an adhesive, and the adhesive includes, by weight, the following raw materials: 75 parts of methacrylic acid, 0.8 parts of polyvinyl alcohol, 11 parts of a strong polar monomer, 55 parts of a polyoctene copolymer emulsion, 5 parts of nano-microcrystalline cellulose, 24 parts of modified nano-titanium dioxide, and 2.8 parts of an aqueous sodium persulfate solution with a mass concentration of 18% , 1.2 parts of ultraviolet absorber, 0.5 parts of dispersant, and 210 parts of deionized water, the strong polar monomer is composed of hydroxyethyl methacrylate, methacrylamide and dimethylaminoethyl methacrylate in a mass ratio of 1:1:3, the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a mass ratio of 3:4, and the dispersant is composed of sodium dodecylbenzene sulfonate, sodium diisooctyl sulfosuccinate and octylphenol polyoxyethylene (10) ether in a mass ratio of 4:5:6.
[0050] The above-mentioned method for preparing a self-adhesive label comprises the following steps:
[0051] S91. Add deionized water and polyvinyl alcohol in a glass reactor according to their mass fractions, introduce high-purity nitrogen, stir at a stirring speed of 350 rpm for 1.2 h, then add methacrylic acid, strong polar monomer, polyoctene copolymer emulsion, nano-microcrystalline cellulose, modified nano-titanium dioxide, ultraviolet absorber and dispersant in sequence, heat to 60°C and keep the temperature constant; then add sodium persulfate aqueous solution with a mass concentration of 18% to initiate the reaction, stop heating after the reaction for 9 h, cool to room temperature, filter, wash, dry, crush and sieve to obtain an adhesive;
[0052] S92, applying adhesive on the surface of the surface layer to obtain an adhesive layer;
[0053] S93, the adhesive layer is combined with the bottom layer, and dried to obtain a self-adhesive label.
[0054] Example 3
[0055] A self-adhesive sticker, wherein the structural layers of the self-adhesive sticker include, from top to bottom, a surface layer (thermal paper with a thickness of 20 μm), an adhesive layer and a bottom layer (wax paper with a thickness of 10 μm); wherein the adhesive layer is prepared from an adhesive, and the adhesive includes, by weight, the following raw materials: 73 parts of methacrylic acid, 0.7 parts of polyvinyl alcohol, 10 parts of a strongly polar monomer, 53 parts of a polyoctene copolymer emulsion, 4.5 parts of nano-microcrystalline cellulose, 22 parts of modified nano-titanium dioxide, and 2. 7 parts, 1 part of ultraviolet absorber, 0.4 parts of dispersant, and 205 parts of deionized water, the strong polar monomer consists of hydroxyethyl methacrylate, methacrylamide and dimethylaminoethyl methacrylate in a mass ratio of 1:1:3, the ultraviolet absorber consists of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a mass ratio of 3:4, and the dispersant consists of sodium dodecylbenzene sulfonate, sodium diethyl sulfosuccinate and octylphenol polyoxyethylene (10) ether in a mass ratio of 4:5:6.
[0056] The above-mentioned method for preparing a self-adhesive label comprises the following steps:
[0057] S91. Add deionized water and polyvinyl alcohol in a glass reactor according to their mass fractions, introduce high-purity nitrogen, stir at a stirring speed of 350 rpm for 1.1 h, then add methacrylic acid, strong polar monomer, polyoctene copolymer emulsion, nano-microcrystalline cellulose, modified nano-titanium dioxide, ultraviolet absorber and dispersant in sequence, heat to 60°C and keep the temperature constant; then add sodium persulfate aqueous solution with a mass concentration of 18% to initiate the reaction, stop heating after the reaction for 9 h, cool to room temperature, filter, wash, dry, crush and sieve to obtain an adhesive;
[0058] S92, applying adhesive on the surface of the surface layer to obtain an adhesive layer;
[0059] S93, the adhesive layer is combined with the bottom layer, and dried to obtain a self-adhesive label.
[0060] Comparative Example 1
[0061] The same as Example 3, except that the amount of polyoctene copolymer emulsion added is 0 part.
[0062] Comparative Example 2
[0063] The same as Example 3, except that an equal amount of nano titanium dioxide with a particle size of 10 nm is used instead of the modified nano titanium dioxide.
[0064] Comparative Example 3
[0065] The same as Example 3, except that: the ultraviolet absorber is dioctadecyl pentaerythritol phosphate.
[0066] Comparative Example 4
[0067] The same as Example 3, except that: the ultraviolet absorber is BASF light stabilizer CHIMASSORB944.
[0068] Comparative Example 5
[0069] The same as Example 3, except that the dispersant is sodium dodecylbenzene sulfonate.
[0070] Comparative Example 6
[0071] The same as Example 3, except that the dispersant is sodium dioctyl sulfosuccinate.
[0072] Comparative Example 7
[0073] The same as Example 3, except that the dispersant is octylphenol polyoxyethylene (10) ether.
[0074] Performance testing
[0075] The self-adhesive labels prepared in the embodiments and comparative examples were tested for the following properties. The specific results are shown in Table 1.
[0076] Not easy to crack: The self-adhesive stickers prepared in the embodiments and comparative examples of the same size were placed in a natural environment for 1 month, 9 months and 18 months, and their cracking state was observed;
[0077] Peel strength and peel strength after aging: Refer to GB / T2792 to test the 180° peel strength, and test it in a UV accelerated aging test box at an irradiation intensity of 1.5Kwh / m 2 , 180° peel strength after 2000h of UV irradiation at 65℃;
[0078] Table 1 Performance test
[0079]
[0080] Analyzing the data in Table 1, we can see that:
[0081] 1) The self-adhesive labels prepared in Examples 1 to 3 have excellent anti-aging properties, thermal stability and adhesion strength, and are not prone to cracking, and are suitable for use in various occasions.
[0082] 2) The performance comparison analysis of the self-adhesive prepared in conjunction with Example 3 and Comparative Example 1 shows that the polyoctene copolymer emulsion prepared by the present application provides long-chain non-polar octane groups, and these long-chain structures can form a kind of "buffer layer" in the adhesive. When the self-adhesive is subjected to external force or environmental changes, this "buffer layer" can absorb and disperse the influence brought by these changes, thereby protecting the adhesive from being destroyed, so that the self-adhesive keeps good adhesion performance and is not easy to crack. In addition, the polyoctene copolymer emulsion also has good synergy with other components. For example, it can enhance the bonding strength of the adhesive together with the strong polar monomer. The strong polar monomer introduces strong polar groups such as amino and amide groups, enhances the bonding strength of the adhesive, and forms forces such as ionic bonds and hydrogen bonds with the oxygen-containing groups on the surface of the surface layer and the bottom layer, while the polyoctene copolymer emulsion provides flexibility, and the combination of the two makes the adhesive have both good adhesion performance and enough flexibility, and is not easy to crack.
[0083] 3) The performance comparison analysis of the self-adhesive prepared in combination with Example 3 and Comparative Example 2 shows that the prepared modified nano titanium dioxide acts as an effective ultraviolet absorber, which can absorb ultraviolet rays and reduce the photodegradation of the self-adhesive caused by UV, thereby improving the anti-aging of the self-adhesive. Through the reaction with substances such as hexamethyldisilazane, 3-aminopropyltrimethoxysilane and tetraethoxysilane, the surface of nano titanium dioxide is modified to have stronger hydrophobic and oil-resistant properties. Through surface modification, the compatibility and dispersibility of nano titanium dioxide in the adhesive are improved, thereby enhancing the anti-aging, thermal stability and adhesion strength of the adhesive.
[0084] 4) The performance comparison analysis of the self-adhesive sticker prepared in combination with Example 3 and Comparative Examples 3-4 shows that the ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a mass ratio of 3:4. When these two ultraviolet absorbers are mixed and used in a specific ratio, a synergistic effect will be produced between them, that is, the effects of the two compounds are superimposed, so that the anti-ultraviolet ability of the self-adhesive sticker is further enhanced. This synergistic effect not only improves the weather resistance of the self-adhesive sticker, prolongs the service life of the product, but also reduces the problems such as color change and material embrittlement caused by ultraviolet radiation, thereby ensuring that the self-adhesive sticker can maintain good performance under various environments. In addition, the ultraviolet absorber used in this combination also helps to improve the overall stability and reliability of the self-adhesive sticker, making it more durable and reliable in practical applications.
[0085] 5) The performance comparison analysis of the self-adhesive adhesive prepared in combination with Example 3 and Comparative Examples 5-7 shows that the dispersant is composed of sodium dodecylbenzene sulfonate, sodium diisooctyl sulfosuccinate and octylphenol polyoxyethylene (10) ether in a mass ratio of 4:5:6. The combined use of these three dispersants can make full use of their respective advantages and act on the particle surface through different mechanisms to achieve a more effective dispersion effect. This synergistic effect not only improves the overall performance of the adhesive, but also helps to improve its processing performance and application performance, such as anti-aging, thermal stability and adhesion strength.
[0086] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A self-adhesive sticker, characterized in that: The structural layers of the self-adhesive adhesive include a surface layer, an adhesive layer and a bottom layer from top to bottom; wherein the adhesive layer is prepared from an adhesive, and the adhesive includes the following raw materials by weight: 70-75 parts of methacrylic acid, 0.6-0.8 parts of polyvinyl alcohol, 9-11 parts of strong polar monomers, 50-55 parts of polyoctene copolymer emulsion, 4-5 parts of nano-microcrystalline cellulose, 20-24 parts of modified nano-titanium dioxide, 2.6-2.8 parts of initiator aqueous solution, 0.8-1.2 parts of ultraviolet absorber, 0.3-0.5 parts of dispersant, and 200-210 parts of deionized water; The strong polar monomer is composed of hydroxyethyl methacrylate, methacrylamide and dimethylaminoethyl methacrylate in a mass ratio of 1:1:3; The preparation method of the polyoctene copolymer emulsion is as follows: 390 parts of deionized water and 0.6 parts of sodium dodecylbenzene sulfonate are added to a glass reactor according to weight fractions, high-purity nitrogen is introduced, and the mixture is stirred at a stirring speed of 300 rpm for 1-1.5 hours, and then 18 parts of 1-octene are added, and the mixture is stirred at a stirring speed of 300 rpm for 0.5-0.7 hours, the mixture is heated to 60° C. and kept at a constant temperature, and then 1 part of an initiator aqueous solution with a weight concentration of 20% is added and reacted at 60° C. for 2-2.5 hours, and then 68 parts of 1-octene, 16 parts of perfluoromethyl vinyl ether, and 5 parts of an ammonium persulfate aqueous solution with a weight concentration of 20% are respectively added dropwise to the reactor through a peristaltic pump, the addition time is 3.5 hours, the mixture is reacted at 60° C. for 5-6 hours, the reaction is completed, the mixture is cooled to room temperature after the reaction is completed, and the mixture is filtered through a 150-mesh screen to obtain the polyoctene copolymer emulsion; The preparation method of the modified nano titanium dioxide comprises the following steps: S41. Fully mix hexamethyldisilazane, 3-aminopropyltrimethoxysilane, tetraethoxysilane and anhydrous ethanol according to their weight fractions to prepare a mixed modifier; S42, according to the mass fraction, 100 parts of nano titanium dioxide with a particle size of 10 nm and 200 parts of the mixed modifier were fully mixed at room temperature for 50-60 minutes, and then ultrasonicated at room temperature for 1-2 hours, and then transferred into a vacuum mixer, heated to 85°C, stirred and refluxed at -0.5MPa for 4-5 hours, and finally ethanol was removed under reduced pressure, and the mixture was dried to obtain modified nano titanium dioxide; The mass ratio of hexamethyldisilazane, 3-aminopropyltrimethoxysilane, tetraethoxysilane and anhydrous ethanol is 2:3:2:100; The ultraviolet absorber is composed of dioctadecyl pentaerythritol phosphate and BASF light stabilizer CHIMASSORB944 in a mass ratio of 3:4; The dispersant is composed of sodium dodecylbenzene sulfonate, sodium dioctyl sulfosuccinate and octylphenol polyoxyethylene (10) ether in a mass ratio of 4:5:6; The mass concentration of the initiator aqueous solution is 18%, and the initiator is sodium persulfate.
2. A method for preparing the self-adhesive label according to claim 1, characterized in that: The following steps are involved: S91. Add deionized water and polyvinyl alcohol in a glass reactor according to their mass fractions, introduce high-purity nitrogen, stir at a stirring speed of 350 rpm for 1-1.2 h, then add methacrylic acid, strong polar monomer, polyoctene copolymer emulsion, nano-microcrystalline cellulose, modified nano-titanium dioxide, ultraviolet absorber and dispersant in sequence, raise the temperature to 60°C and keep the temperature constant; then add an initiator aqueous solution to initiate the reaction, stop heating after the reaction for 9 hours, cool to room temperature, filter, wash, dry, crush and sieve to obtain an adhesive; S92, applying adhesive on the surface of the surface layer to obtain an adhesive layer; S93, the adhesive layer is combined with the bottom layer, and dried to obtain a self-adhesive label.
3. Use of the self-adhesive sticker as claimed in claim 1 in label stickers.
Citation Information
Patent Citations
Method for preparing fluorine-containing polymer by using mixed fluorine-containing surfactant
CN103204961A
Bis-diaminophenyl compound, crosslinking agent, composition, and molded article
CN117255779A